2016
DOI: 10.2196/games.5678
|View full text |Cite
|
Sign up to set email alerts
|

Game On? Smoking Cessation Through the Gamification of mHealth: A Longitudinal Qualitative Study

Abstract: BackgroundFinding ways to increase and sustain engagement with mHealth interventions has become a challenge during application development. While gamification shows promise and has proven effective in many fields, critical questions remain concerning how to use gamification to modify health behavior.ObjectiveThe objective of this study is to investigate how the gamification of mHealth interventions leads to a change in health behavior, specifically with respect to smoking cessation.MethodsWe conducted a qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 27 publications
2
75
0
Order By: Relevance
“…The findings of this study offer relevant and potentially provocative insights into effective app design for digital mHealth apps [19,20]. In particular, the findings related to which elements of app design are more conducive to smoking cessation are intriguing and extend current knowledge about the design of evidence-based smoking cessation mHealth apps [25].…”
Section: Extending Extant Knowledgementioning
confidence: 72%
See 2 more Smart Citations
“…The findings of this study offer relevant and potentially provocative insights into effective app design for digital mHealth apps [19,20]. In particular, the findings related to which elements of app design are more conducive to smoking cessation are intriguing and extend current knowledge about the design of evidence-based smoking cessation mHealth apps [25].…”
Section: Extending Extant Knowledgementioning
confidence: 72%
“…For instance, studies have shown that aspects of gamification can be twice as effective in frequency of self-monitored exercise for weight loss program compared to a standard paper diary [18]. Ultimately, applications that incorporate behavior change techniques tend to be associated with increased intervention effectiveness [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…money or presents) do not come into question in case of such prevention programs. Based on the findings of ElHilly and colleagues [57], it is intrinsic motivation that may function as a positive drive to engagement in a prevention program and to a positive health behavior as well, while external social influences might rather have a negative impact on the overall efficacy of gamification. Similar results were published by Habgood and Ainsworth [58], indicating that in-game intrinsic motivators are more effective than extrinsic ones in case of educational games.…”
Section: Discussionmentioning
confidence: 99%
“…Social media may allow dental professionals to deliver the help outside a dental practice environment. Notably, some features of social media such as gamification [29,30] and engaging website design [31] may be particularly relevant to address and inform patients about critical health-related issues and educate them, which can also help increase their trust and appreciate the level of service received [32][33][34]. Research studying the role of how social media may help reduce patients' dental anxiety is a worthwhile and exciting endeavor.…”
Section: Limitations and Future Researchmentioning
confidence: 99%